Natural History of Early Repolarization in the Inferior Leads - Stein, Ricardo (Ann Noninvasive Electrocardiol, 2012)
Aims: Though early repolarization (ER) in the inferior leads has been associated with increased cardiovascular risk, its natural history is uncertain. We aimed to study the serial electrocardiographic behavior of inferior ER and understand factors associated with that behavior. Methods: We selected electrocardiograms (ECGs) from patients with the greatest amplitude of ER in AVF from ECGs of 29,281 ambulatory patients recorded between 1987 and 1999 at the Palo Alto Veterans Affairs Hospital. Starting from the highest amplitude, we reviewed the ECGs and medical records from the first 85%. From this convenience sample, 36 were excluded for abnormal patterns similar to ER. The remaining 257 patients were searched for another ECG at least 5 months later, of whom, 136 satisfied this criteria. These ECGs were paired for comparison and coded by four interpreters. Results: The average time between the first and second ECGs was 10 years. Of the 136 subjects, 47% retained ER while 53% no longer fulfilled the amplitude criteria. While no significant differences were found in initial heart rate (HR) or time interval between ECGs, those who lost the ER pattern had a greater difference in HR between the ECGs. There was no significant difference in the incidence of cardiovascular events or deaths. Conclusions: In conclusion, the ECG pattern of ER was lost over 10 years in over half of the cohort. The loss of ER was partially explained by changes in HR, but not higher incidence of cardiovascular events or death, suggesting the entity is a benign finding.